Conserving biodiversity through certification of tropical agroforestry crops at local and landscape scales - Tscharntke, Teja; Milder, Jeffrey C.; Schroth, Götz; Clough, Y.; DeClerck, Fabrice A.J.; Waldron, A.; Rice, R.; Ghazoul, J. (Wiley, 2015)
Voluntary sustainability standards and certification offer a promising mechanism to mitigate the severe negative impacts of agricultural expansion and intensification on tropical biodiversity. From a conservation standpoint, certification of tropical agroforestry crops, especially coffee and cocoa, is of particular interest given the potentially high biodiversity value of agroforestry systems and the substantial market penetration of coffee and cocoa certification in recent years. Here, we review experience with coffee and cocoa certification, summarize evidence on conservation impacts, and explore future needs. While there is much evidence that environmental criteria behind certification support biodiversity conservation, it is less clear to what extent certification is the cause of improved conservation outcomes. Additionally, the farm-scale focus of current certification models may limit delivery of biodiversity conservation benefits, as maintenance of biodiversity depends on processes at larger landscape scales. To address this scale mismatch, we suggest that investment and innovation in certification over the next decade prioritize landscape conservation outcomes. This may be achieved by (1) linking existing certification mechanisms with broader landscape and ecosystem service management approaches and/or (2) expanding current certification models to consider the landscape itself as the certified unit.